2018
DOI: 10.1186/s12904-018-0370-9
|View full text |Cite
|
Sign up to set email alerts
|

Talk CPR - a technology project to improve communication in do not attempt cardiopulmonary resuscitation decisions in palliative illness

Abstract: BackgroundA national Do Not Attempt Cardiopulmonary Resuscitation policy was rolled out for the National Health Service in Wales in 2015. A national steering group led on producing information videos and a website for patients, carers and healthcare professionals, forming part of a quality improvement program. Videos were planned, scripted and produced with healthcare professionals and patient/carer representatives, and were completed with both English and Welsh language versions. The TalkCPR videos encourage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 7 publications
0
23
0
4
Order By: Relevance
“…Therefore, the general public might overestimate the success rate of CPR and the benefit of parenteral nutrition and hydration in late-stage cancer patients. A recent study found that specific information videos and websites regarding LST for the general public, such as the Talk CPR project, which provides knowledge regarding CPR [29], are helpful to reduce the dissonance between the general public and healthcare providers. Such information provision may also encourage patients and caregivers to approach their healthcare provider about this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the general public might overestimate the success rate of CPR and the benefit of parenteral nutrition and hydration in late-stage cancer patients. A recent study found that specific information videos and websites regarding LST for the general public, such as the Talk CPR project, which provides knowledge regarding CPR [29], are helpful to reduce the dissonance between the general public and healthcare providers. Such information provision may also encourage patients and caregivers to approach their healthcare provider about this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, healthcare providers should address the expectations of patients with advanced cancer about aggressive treatment, LST, and limited medical care to initiate and facilitate EOL discussion. A recent study suggested that providing specific information through different modalities can improve the confidence and understanding of healthcare providers regarding EOL discussion, and adding such information to existing education programs is considered effective [29].…”
Section: Discussionmentioning
confidence: 99%
“…In Wales, UK, a new approach to tackle the sensitive issue of DNACPR discussions was developed in 2015 called “TalkCPR” [23]. This educational program included websites, videos and media pads aimed at both patients and healthcare professionals [23].…”
Section: Discussionmentioning
confidence: 99%
“…In Wales, UK, a new approach to tackle the sensitive issue of DNACPR discussions was developed in 2015 called “TalkCPR” [23]. This educational program included websites, videos and media pads aimed at both patients and healthcare professionals [23]. This approach was very successful, and physicians exposed to the education reported that they discussed DNACPR more frequently with their patients and felt more comfortable with the discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation